Mindfulness interventions in schools: Integrity and feasibility of implementation. (January 2020) - Emerson, Lisa-Marie; de Diaz, Natalja Nabinger; Sherwood, Ashra; Waters, Allison; Farrell, Lara
Research on mindfulness-based interventions (MBIs) has proliferated in recent years and the integration of mindfulness-based programs in school settings has been at the forefront of implementation research. Recent reviews of studies evaluating the efficacy of school-based mindfulness programs have produced mixed findings, which may in part be due to methodological differences across studies to date, as well as adaptations of MBIs in order to implement them within school settings. For example, there are vast differences across studies in the content, delivery, and training requirements of school-based MBIs, which may influence both fidelity and efficacy. This systematic review aimed to synthesize the literature on the implementation of school-based MBIs and determine the degree to which the interventions align to standards for MBIs. A systematic search identified studies evaluating the effects of a school-based MBI on mental health outcomes in schools, utilizing quantitative and qualitative designs. The results draw comparison across the identified MBIs in relation to intervention integrity, and teacher training and competence according to existing standards. The findings indicate a poor alignment to all standards; for example, intervention integrity was indicated in 45% of studies that included core mindfulness practices, and standards of teacher training were met in 26% of studies. In addition, the feasibility design of studies is critiqued against recommended standards. Despite claims from many studies, feasibility has not yet been established for school settings. Feasibility studies have failed to adequately assess organizational factors that influence implementation. The lack of detail and consistency in reporting across studies is a particular limitation of the field of research, which may have disadvantaged the assessment of studies against stringent guidelines. The ongoing challenges to developing an evidence base for school-based MBIs as well as to implementation are discussed. Recommendations for future directions in implementation science of mindfulness interventions within a school context are provided.